2019
DOI: 10.1002/jhet.3725
|View full text |Cite
|
Sign up to set email alerts
|

NO2‐Fe (II)Pc‐catalyzed synthesis of 2‐ferrocenyl‐5‐aryl‐1,3,4‐oxadiazoles and study of antifungal activity

Abstract: Six novel derivatives of 2‐ferrocenyl‐5‐aryl‐1,3,4‐oxadiazoles have been synthesized through catalytic oxidation of benzoylhydrazone with nitrophthalocyanine iron (II) as catalyst and tert‐butyl hydroperoxide as oxidant. All of the compounds have been characterized by high‐resolution mass spectrometry, 1H, 13C NMR, and infrared spectroscopy. Moreover, the antifungal activities of all new compounds have been evaluated and the results showed that the compounds exhibited excellent antifungal activities. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Both 18b and 18e can be considered as promising drugs for further investigation. 58 Recently, four FCZ ferrocenyl derivatives with one triazole moiety replaced by different alkyl substituents were developed in our group. The stability of these complexes in deuterated DMSO and H 2 O -common media for preparation of stock solutions for biological screeningwere monitored by NMR spectroscopy and showed that all tested compounds were stable for up to 24 hours in solution.…”
Section: Metallocenyl-derivatives Of Azole Antifungal Drugsmentioning
confidence: 99%
“…Both 18b and 18e can be considered as promising drugs for further investigation. 58 Recently, four FCZ ferrocenyl derivatives with one triazole moiety replaced by different alkyl substituents were developed in our group. The stability of these complexes in deuterated DMSO and H 2 O -common media for preparation of stock solutions for biological screeningwere monitored by NMR spectroscopy and showed that all tested compounds were stable for up to 24 hours in solution.…”
Section: Metallocenyl-derivatives Of Azole Antifungal Drugsmentioning
confidence: 99%
“…One issue that the authors noted, in addition to the small number of systematic studies into antifungal metal complexes, is the lack of mode of action studies and the often less than ideal antifungal data collection and reporting with regard to methodology and controls. Furthermore, there are only a few studies reporting in vivo evaluation of antifungal metal-based compounds. ,,,,, A series of phenanthroline complexes containing copper, manganese, or silver showed no toxicity in a G. mellonella (moth larvae) in vivo model at 10 μg/larva, and most complexes reduced the fungal burden of larvae infected with Candida haemulonii. , Silver complexes of 1,10-phenanthroline-5,6-dione protected G.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are only a few studies reporting in vivo evaluation of antifungal metal-based compounds. 28,30,35,51,53,54 A series of phenanthroline complexes containing copper, manganese, or silver showed no toxicity in a G. mellonella (moth larvae) in vivo model at 10 μg/larva, and most complexes reduced the fungal burden of larvae infected with Candida haemulonii. 41,53 Silver complexes of 1,10-phenanthroline-5,6-dione protected G. mellonella larvae from infection with Phialophora verrucose.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Only a couple of studies so far have reported the in vivo evaluation of metal-based compounds. 28,30,35,51,[53][54] Gandra et al studied a series of phenanthroline complexes containing copper, manganese and silver. They demonstrated that these compounds showed no toxicity in a Galleria mellonella (moth larvae) in vivo model at 10 µg/larva.…”
Section: Introductionmentioning
confidence: 99%